Comparing the Effectiveness of Methods and Solvents on the Yield and Phytochemicals of Gerga Citrus Peel Essential Oil (Citrus nobilis L. Var RGL) from Kerinci Regency - Noviarni, Intan; Hartati, Nina (Program Studi Kimia, Universitas Lambung Mangkurat, 2024)
Gerga orange was one of the leading commodities of Bengkulu province and also widely cultivated in Kerinci, Jambi. Nearly 75% of gerga orange peel was wasted without any processing. Orange peel was a plant that can be produced in to essential oil. However, the extraction effectiveness can be affected by the solvent and method. The purpose of this study was to determine the best solvent and method for extracting gerga orange peel essential oil. In addition, this research also aims to analyze the phytochemicals and yield. In this study, maceration and soxhletation methods will be compared to extract gerga orange peel essential oil with a variety of solvents with different polarities. The simplicia was macerated with ethanol, ethyl acetate and n-hexane solvents respectively for 3x24 hours. Then it was distilled to evaporate the ethanol. While the soxhletation method was conducted by soxhleted the simplicial for 4 hours. The results obtained yield of gerga orange peel essential oil by maceration method with ethanol, ethyl acetatee, n-hexane solvents, respectively, 23.04%; 16.05%; 11.80%, whereas with the soxhletation method 10.36%; 3.02%; and 2.04%. The maceration method with ethanol solvent was more effective for extracting the essential oil of gerga orange peel. Based on phytochemical screening the main secondary metabolites in the essential oil of gerga orange peel were phenolic and flavonoid. There was no saponin detected in the essential oil of gerga orange peel.Keywords: maceration, soxhletation, Citrus nobilis L. Var RGL, phytochemicals